A Literature Review On Turnover Intention Analysis: The Effect Of Leadership Style, Compensation, and Work Environment - Gurawan Dayona Ismail; Lia Agustianti Ghemy (Universitas Indonesia Membangun (Inaba), 2026)
Employee turnover intention remains a persistent challenge for organizational sustainability, yet recent studies often examine leadership style, compensation, and work environment in isolation rather than in an integrated framework. This literature review seeks to address this gap by synthesizing findings from fifteen peer-reviewed articles published between 2022 and 2025. A systematic review approach was employed, with inclusion criteria focusing on empirical studies that explicitly analyzed the three variables in relation to turnover intention. The synthesis reveals consistent patterns: authoritarian leadership tends to heighten turnover intention, while transformational, participative, and supportive leadership styles mitigate it; compensation fairness and adequacy are repeatedly linked to reduced turnover intention; and positive work environments characterized by inclusivity, safety, and work–life balance foster retention, whereas stressful or unsupportive climates intensify turnover risks. Notably, several studies highlight tensions between compensation adequacy and leadership style, suggesting that supportive leadership may partially offset compensation dissatisfaction. By integrating these variables, the review contributes theoretically by clarifying how leadership, compensation, and environment interact as complementary retention mechanisms, and practically by underscoring the need for holistic HRM (Human Resource Management) strategies that combine leadership development, equitable compensation systems, and supportive workplace cultures